Design of a novel multiepitope vaccine against glioblastoma by in silico approaches - Sako Mirzaie; Kevin Da Yuan; Heyu Ni; Xiao Yu Wu (Scientific Reports)
Abstract Glioblastoma (GBM) is the most common malignant primary brain tumor, with a median survival rate of less than two years. Currently, there is no cure for GBM, underscoring the urgent need for innovative treatment approaches. Vaccine design emerges as a crucial strategy, offering a safe and effective means for both preventive and therapeutic interventions against GBM. In this study, we targeted four GBM-associated mutated surface proteins—urokinase plasminogen activator surface receptor (PLAUR), integrin beta-3 (ITGB3), and the B-41 alpha chain (HLA-B) and A-24 alpha chain (HLA-A) of the HLA class I histocompatibility antigens—to design a peptide-based vaccine. The vaccine construct includes cytotoxic T lymphocyte (CTL) and T helper cell (Th cell) epitopes, and was meticulously evaluated for antigenicity, allergenicity, and toxicity. The results indicate that the vaccine is antigenic and non-allergenic, making it a promising candidate. Additionally, the physicochemical properties of the vaccine suggest stability and suitability for further development. Immune simulation studies predict a strong immune response upon vaccine administration. Our vaccine shows promise as a potential tool in the fight against GBM, offering new hope for patients facing this devastating disease.